The breast cancer working group presentation was divided into three sections: the epidemiology, pathology and treatment of breast cancer - Toi, M.; Ohashi, Y.; Seow, A.; Moriya, T.; Tse, G.; Sasano, H.; Park, B.W.; Chow, L.W.C.; Laudico, A.V.; Yip, C.H.; Ueno, E.; Ishiguro, H.; et al. (Oxford University Press, 2010)
Epidemiology of breast cancer: The incidence and mortality of breast cancer are lower in Asia than in the West, particularly in post-menopausal women, but they are increasing. The age patterns of the incidence of breast cancer in Asia differ from in the West: in most Asian countries the peak incidence of breast cancer is at about age 45-50, whereas in western countries the incidence continues to increase even at older ages. Mortality is decreasing in western countries, whereas it is still increasing in Asian nations. There are many epidemiological factors involved in breast cancer, and important known risk factors include diet, obesity and diabetes. Asian studies found that high intake of isoflavones reduced the risk of breast cancer. Pathology of breast cancer: With regard to the pathology of breast cancer, for the molecular subtype, luminal A and luminal B are being used, while HER2 expression and rapid proliferation are also employed. Study results showed a somewhat higher prevalence of luminal A in Japanese compared with Americans. Ductal carcinoma in situ breast cancer is less frequent in Asian breast cancer patients than in Americans. The Working Group resolved to establish an international committee for pathological assessment of breast cancer in Asia. Treatment of Breast Cancer: Pharmacokinetics-pharmacodynamics studies are needed between ethnic backgrounds, investigating aromatase inhibitors and tamoxifen (endoxifen), as well as the effects of demographic factors such as diet, medical care, body mass index, etc. Correlations between adverse events and the clinical outcome also need to be studied.